Practical Electronics/Series RC

Series RC

A circuit of two components R and C connected in series Circuit analysis

Circuit's Impedance

In Rectangular coordinate

• $Z=Z_{R}+Z_{C}$ $Z=R+{\frac {1}{j\omega C}}={\frac {1}{j\omega C}}(1+j\omega T)$ $T=RC$ In Polar coordinate

• $Z=Z_{R}+Z_{C}$ $Z=R\angle 0+{\frac {1}{\omega C}}\angle -90=|Z|\angle \theta ={\sqrt {R^{2}+({\frac {1}{\omega C}})^{2}}}\angle Tan^{-}1{\frac {1}{\omega RC}}$ $Tan\theta ={\frac {1}{\omega RC}}={\frac {1}{2\pi fRC}}={\frac {t}{2\pi RC}}$ The value of $\theta ,\omega ,f$ depend on the value of R and C . Therefore, when the value of R or C changed the value of Phase angle difference between Current and Voltage, Frequency, and Angular of Frequency also change

$\omega ={\frac {1}{Tan\theta RC}}$ $f={\frac {1}{2\pi Tan\theta RC}}$ $t=2\pi Tan\theta RC$ Circuit's Response

Natural Response of the cicuit can be obtained by setting the differential equation of the circuit to zero

$L{\frac {di}{dt}}+iR=0$ ${\frac {di}{dt}}=-{\frac {R}{L}}i$ $\int {\frac {di}{i}}=-{\frac {R}{L}}\int dt$ $Lni=-({\frac {R}{L}})t+e^{c}$ $i=Ae^{-}({\frac {R}{L}})t$ $i=Ae^{-}({\frac {t}{T}})$ $A=e^{c}={\frac {V}{R}}$ $T=RC$ The natural response of the circuit is an exponential decrease